A Genome-wide association study of fertility and maternal traits in South African Bonsmara cattle - Van Marle Koster, Este (University of Pretoria, 2020)
Dissertation (Msc Agric Animal Science (Animal Breeding and Genetics))--University of Pretoria, 2020.